2010
DOI: 10.2341/09-353-s
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise Excavation in a Permanent Molar: 17-year Follow-up

Abstract: Due to the risk of pulp exposure in deep carious lesions, stepwise excavation can be a conservative and successful option for selected cases, when signs and symptoms of a normal pulp are present. FF Lima • RC Pascotto • AR BenettiStepwise Excavation in a Permanent Molar:17-year Follow-up SUMMARYThe current study presents a 17-year clinical report of stepwise excavation and indirect pulp capping in a lower right first molar, with great dentin destruction and a lack of dentin support of the cusps. At the first a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
0
5
0
1
Order By: Relevance
“…Stepwise (incomplete caries removal in two steps) and complete caries excavation [5]. Statistics from literature [6,7] has shown that in comparison to complete caries removal, there is atleast 73% to 95% [6,7] success rate with different techniques of indirect pulp capping like step-wise removal (SWR) [8][9][10] of caries and partial caries removal (PCR) at a single visit [3] which has shown 82% better results as compared to SWR (62%) [6].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Stepwise (incomplete caries removal in two steps) and complete caries excavation [5]. Statistics from literature [6,7] has shown that in comparison to complete caries removal, there is atleast 73% to 95% [6,7] success rate with different techniques of indirect pulp capping like step-wise removal (SWR) [8][9][10] of caries and partial caries removal (PCR) at a single visit [3] which has shown 82% better results as compared to SWR (62%) [6].…”
Section: Resultsmentioning
confidence: 99%
“…A 17 year old follow up case study [9] has favored stepwise excavation -which is partial removal of the carious lesion which is then lined with Calcium hydroxide and bulk filled with Zinc oxide eugenol [10]. After 45 days the lesion is revisited and given a Glass Ionomer restoration.…”
Section: Review Of the Materials And Methods Of Indirect Pulp Cappingmentioning
confidence: 99%
See 1 more Smart Citation
“…10 yıllık süreçte tatmin edici marjinal uyum gözlenmiĢ, ağrı, hassasiyet ve periapikal radyolusensi gözlenmemiĢtir. 129 17 yıllık takip sonucunda pulpanın vitalitesinin korunduğu bildirilmiĢtir. Bir baĢka çalıĢma-da aĢamalı çürük tedavisi yapılan diĢlerde baĢarılı tedavi oranı %74.1, çürüğün tamamen uzaklaĢtırıldığı diĢlerde de %62.4 olarak tespit edilmiĢtir.…”
Section: Aģamalı çüRük Tedavisi (Stepwise Excavation Technique)unclassified
“…A routine practice is to limit caries excavation to the outer infected dentin and maintain the remineralizable affected dentin. 19 Recent endeavors in biomineralization, repair, and regeneration of hard dental tissues have accomplished enormous goals and created novel technologies. 20 The first section of this Review reports on some relevant compositional and developmental features of mineralized tooth structures to provide the basic knowledge for understanding current strategies of remineralizing, regenerating, and repairing natural tooth structural defects that are subsequently elaborated in successive sections.…”
Section: Introductionmentioning
confidence: 99%